Observation of the root surfaces and analysis of the mineral contents in cementum of patients with rapidly progressive periodontitis - Zhu, Xiao-ling; Meng, Huan-xin (Zhonghua kouqiang yixue zazhi, 2003)
To observe root surfaces and analyze the mineral contents in cementum of patients with rapidly progressive periodontitis (RPP). Ten teeth were selected from RPP patients, adult periodontitis (AP) patients and healthy (H) control subjects respectively, and prepared for scanning electron microscopy (JSM-35C). The energy-dispersive X-ray analysis was used to measure the mineral contents in cementum (Ca, P, Mg). The root surfaces of RPP teeth were similar to that of AP teeth. Ca: 64.60% +/- 2.29% vs 63.54% +/- 2.97%, P > 0.05; P: 32.54% +/- 1.29% vs 32.97% +/- 2.40%, P > 0.05; Mg: 2.86% +/- 1.29% vs 3.48% +/- 1.02%, P > 0.05; Ca/P: 2.00 +/- 0.17 vs 1.95 +/- 0.25, P > 0.05. There were no differences in Ca, P, Mg contents and Ca/P ratio between RPP teeth and AP teeth. There may not be cementoplasia in a part of RPP teeth.